Teaching Campus Optimization Using ICT As A Social Education Movement Building Education In Undeveloped Villages - Sembiring, Afen Prana Utama; Dessyana, Dessyana (Asia Pacific Journal of Management and Education (APJME), 2023)
SD PAB 25 in supporting an effective 2013 curriculum, the process of academic activity in which the subject teacher gives a recap of scores to each homeroom teacher to be inputted back in the final grade as a report card, the length of time to search for data in the process, besides that the student assessment processing system is still manual. Thus, the manual process by recording it in the book can cause damage or loss of data that will later be needed when making the report card. Therefore, this research was conducted in order to answer these needs in schools in underdeveloped villages. We use the system development cycle as the research method. The design of input, output, menus, and database displays uses Sublime Text and the Javascript programming language, using the Mongo DB Database Management System. The resulting output is in the form of report cards. The results of the study showed that the PSB model can facilitate students and teachers at school. Moreover, it is very important to be implemented in schools.